Expertise and injury experience in professional skiers modulate the ability to predict the outcome of observed ski-related actions. (January 2022) - Rossi Sebastiano, Alice; Poles, Karol; Biggio, Monica; Bove, Marco; Neppi-Modona, Marco; Garbarini, Francesca; Fossataro, Carlotta
Abstract: Professional athletes, compared to beginners, can better predict the outcome of sport-related observed movements, via mirror motor-system modulations (motor resonance). Furthermore, motor-system inhibition occurs when observing other people experiencing pain (pain resonance). Here we investigated whether observing sport-related actions, whose outcome can lead or not to a painful experience, results into different prediction performances depending on expertise and history of injury. Experiment 1 revealed that professional skiers, relative to beginners, show greater prediction accuracy but slower reaction times. Experiment 2 revealed that, among professional skiers, those previously injured, compared to uninjured ones, are slower in predicting the outcome of the observed action when it actually leads to an injury. We hypothesize that such results could be explained by an automatic activation of both motor and pain resonance mechanisms in the onlooker, inducing a sort of experience-dependant freezing response while observing actions likely leading to an injury. Highlights: We address if motor expertise and pain experience affect motor and pain resonance. Accuracy & reaction time are collected in beginners and professional skiers (Exp1). Accuracy & reaction time are collected in injured and non-injured athletes (Exp2). Motor expertise enhances prediction accuracy of ski-related action outcome. Pain experience boosts the ability to anticipate an injury via a freezing reaction.